Overnight transdermal scopolamine patch administration has no clear effect on cognition and emotional processing in healthy volunteers - Browning, M; Cowen, P; Harmer, C; Bukala, B; Murphy, S (SAGE Publications, 2018)
There has been increasing interest in the antidepressant effects of the muscarinic cholinergic receptor antagonist scopolamine. Here we assess, for the first time, whether a transdermal scopolamine patch is sufficient to induce changes in cognition that are consistent with the reported cognitive and antidepressant effects of scopolamine. A scopolamine or placebo patch was administered to healthy volunteers [n=33] for 17h in a double-blind, between-subject procedure. There was no clear effect of scopolamine patch on emotional cognition, verbal or working memory, suggesting that the effective dose of scopolamine available through the patch is too low to represent a viable antidepressant mechanism.